A randomized, phase 1, placebo‐controlled trial of APG‐157 in oral cancer demonstrates systemic absorption and an inhibitory effect on cytokines and tumor‐associated microbes. Issue 8 (5th February 2020) - Basak, Saroj K.; Bera, Alakesh; Yoon, Alexander J.; Morselli, Marco; Jeong, Chan; Tosevska, Anela; Dong, Tien S.; Eklund, Michael; Russ, Eric; Nasser, Hassan; Lagishetty, Venu; Guo, Rong; et al.
Abstract : Background: Although curcumin's effect on head and neck cancer has been studied in vitro and in vivo, to the authors' knowledge its efficacy is limited by poor systemic absorption from oral administration. APG‐157 is a botanical drug containing multiple polyphenols, including curcumin, developed under the US Food and Drug Administration's Botanical Drug Development, that delivers the active components to oromucosal tissues near the tumor target. Methods: A double‐blind, randomized, placebo‐controlled, phase 1 clinical trial was conducted with APG‐157 in 13 normal subjects and 12 patients with oral cancer. Two doses, 100 mg or 200 mg, were delivered transorally every hour for 3 hours. Blood and saliva were collected before and 1 hour, 2 hours, 3 hours, and 24 hours after treatment. Electrocardiograms and blood tests did not demonstrate any toxicity. Results: Treatment with APG‐157 resulted in circulating concentrations of curcumin and analogs peaking at 3 hours with reduced IL‐1β, IL‐6, and IL‐8 concentrations in the salivary supernatant fluid of patients with cancer. Salivary microbial flora analysis showed a reduction in Bacteroidetes species in cancer subjects. RNA and immunofluorescence analyses of tumor tissues of a subject demonstrated increased expression of genes associated with differentiation and T‐cell recruitment to the tumor microenvironment. Conclusions: The results of the current study suggested that APG‐157 could serve as a therapeutic drug in combination with immunotherapy. Lay Summary: Curcumin has been shown to suppress tumor cells because of its antioxidant and anti‐inflammatory properties. However, its effectiveness has been limited by poor absorption when delivered orally. Subjects with oral cancer were given oral APG‐157, a botanical drug containing multiple polyphenols, including curcumin. Curcumin was found in the blood and in tumor tissues. Inflammatory markers and Bacteroides species were found to be decreased in the saliva, and immune T cells were increased in the tumor tissue. APG‐157 is absorbed well, reduces inflammation, and attracts T cells to the tumor, suggesting its potential use in combination with immunotherapy drugs. Abstract : When delivered transorally, curcumin and its analogues in APG‐157 are absorbed into the blood and tumor tissue, with an inhibitory effect noted on salivary Bacteroides species, possibly through decreases in NF‐κB–driven inflammatory cytokines. Immune cell recruitment to the tumor cell microenvironment indicates that APG‐157 could serve as a neoadjuvant therapeutic drug.